(untitled) (Biological Sciences - PJSIR, 2009)
Mean values of copper, manganese, nickel and zinc in different cigarette brands sold in Pakistan were found to be in the range of 8.61 to 94.67 ?g/g, 26.40 to 98.20 mg/g, 0.61 to 8.58 mg/g and 16.92 to 99.60 mg/g, respectively, through Atomic Absorption Spectrophotometer (AAS). The results are discussed with reference to and in comparison with the mean average concentration of these elements reported in the cigarettes of other countries.